Kurdish Studies Archive : Vol. 6 No. 2 2018 - Bruinessen, Martin van (Brill, 2018)
Kurdish Studies Archive publishes the content of volumes 1 to 10 of Kurdish Studies . This interdisciplinary and peer-reviewed journal was dedicated to publishing high-quality research and scholarship. Since 2023 the journal has been continued as the new Kurdish Studies Journal , published by Brill, and focuses on research, scholarship, and debates in the field of Kurdish studies in a multidisciplinary fashion covering a wide range of topics including, but not limited to, economics, history, society, gender, minorities, politics, health, law, environment, language, media, culture, arts, and education.